Nutritional Control of Ascosporogenesis in an Apomictic Strain of Saccharomyces cerevisiae - Bilinski, Anthony Carl (My University, 1979)
An unusual strain of Saccharomyces cerevisiae that produces two-spored asci under conditions in which typical strains produce three and four-spored asci was investigated. It was possible to restore "normal" three and four-spored ascus production in this strain by manipulating the nutritional environment. The effects of nutritional factors supplied during the presporulation and sporulation phases were studied. The change in the proportion of three and four-spored asci was the major parameter employed to quantitate the effect of these factors on ascosporogenesis. Using the Giemsa nuclear stain, germination techniques, and genetic analysis, the number of spores per ascus was related to the manner of nuclear division in developing asci.
Keywords: Biology; Biology